Pro Novell Open Enterprise Server - van Vugt, Sander; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2005)
Novell's best-selling server software has been reinvented in Linux! And the Novell Open Enterprise Server features the best of both worlds, including top features from NetWare Components, SUSE Linux Enterprise Server 9 Components, and Novell Services. Author Sander van Vugt comprehensively covers this server product, and takes you through all of the necessary setup stages to get your server running. He discusses the core features like eDirectory, Novell Storage Services, iPrint, and iManager. van Vugt also examines vital administration topics like software management and security, and services like Virtual Directory, Clustering, and Apache Web Server. He also provides an overview of CLE certification, and strategies to prepare for it. Note that this book covers both the Netware and Linux versions of Open Enterprise Server.
Getting Started -- to Open Enterprise Server -- Installing Open Enterprise Server -- Upgrading to Open Enterprise Server -- to SUSE Linux Enterprise Server -- to the NetWare Kernel -- Connecting to Open Enterprise Server -- Open Enterprise Server Management Utilities -- Core Services -- eDirectory Management -- Managing the User Environment -- File Access -- Configuring Volumes -- Managing Security -- OES Software Management -- Networking Open Enterprise Server -- Managing iPrint -- Open Enterprise Server Web-Based Services -- The Apache Web Server -- Using Virtual Office -- Advanced Services -- Nsure Identity Manager -- to Novell Clustering Services -- Using OpenWBEM for Server Health Monitoring.
Keywords: Open source software; Computer programming; Software engineering; Open Source; Software Engineering/Programming and Operating Systems